Kebijakan Direktur Akbid Menara Bunda Kabupaten Kolaka Dalam Pembinaan Akhlak Islam Mahasiswi - Arifin, Muhammad; Putra, Zulfikar; Wajdi, Farid (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Islam is a religion that highly upholds noble character, and this is affirmed in the hadith of the Prophet Sallallahu Alaihi Wasallam (SAW) stating that the main purpose of his being sent to the human race is to perfect commendable character. Students as critical intellectuals who are characteristic of academics, need to have a commitment to the teachings of religion (Islam) and morality, which of course is supported by policies implemented by the campus. This study discusses the policies carried out by the Director of the Kolaka Nursing Academy in Islamic Student Moral Development. The purpose of this study is to analyze the policies applied by the Kolaka Nursing Academy Director in the Islamic Student Moral Development, supporting and inhibiting factors in Islamic Moral Development students at Kolaka Nursing Academy, Effective solutions to increase students' importance on the value of diversity on campus and life daily. This type of research is qualitative with descriptive analysis. From this study, it was produced that the policy in developing the Islamic character of Kolaka Nursing Academy students was carried out through 3 (three) stages, namely first, agenda-setting. second, the implementation of the quality target program as a manifestation of the policy implementation of the Kolaka Nursing Academy Director to foster students' Islamic behavior, and the third evaluation of supporting factors for the development of Islamic students, including environmental (campus, and community) factors.